ON THE CONCEPT OF COMMUNICATIVE POTENTIAL (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the concept of communicative potential from the perspective of the interaction between verbal and nonverbal means in the speech production process. While traditional structural linguistics primarily focused on language as a closed and autonomous system, contemporary anthropocentric approaches emphasize the role of the speaker as an active participant in communication. In this regard, speech is interpreted not merely as the realization of linguistic possibilities but also as a psychophysiological and sociocultural phenomenon shaped by both verbal and nonverbal factors.The study analyzes how communicative competence and communicative potential are manifested through the speaker's social status, educational background, life experience, worldview, and accumulated social knowledge. Particular attention is paid to the role of nonverbal factors, including gestures, facial expressions, prosodic features, and other extralinguistic means, in the formation and interpretation of speech. Drawing upon theoretical perspectives proposed by D. Hymes, M. Canale and M. Swain, S. Akhmanova, and other scholars, the article argues that effective communication depends not only on grammatical competence but also on the speaker's ability to appropriately select and combine verbal and nonverbal resources according to the communicative situation.
Keywords: Communicative potential; communicative competence; verbal means; nonverbal means; speech production; speech act; social knowledge; anthropocentric linguistics; psychophysiological processes; discourse; communication; extralinguistic factors.